Wrong turn ebook - Fanning, Diane (Lucinda Pierce, 2018)
In this "fast-paced mystery" from an Edgar Award finalist, detective Lucinda Pierce must confront the possibility that she put the wrong person in prison ( Booklist ). Homicide investigator Lucinda Pierce's confidence in her own judgment is deeply shaken when she learns that a woman she helped to put away for the murder of her stepdaughter may not be guilty. The girl's remains have been found—along with four other bodies—in the basement of a serial killer. At the same time Lucinda hears that US Representative Chris Phillips, in prison for killing his third wife, is out on bond, awaiting a new trial, and terrorizing his previous ex-wife. He too was originally convicted based on Lucinda's evidence. Then her young friend, middle-schooler Charley Spencer, is arrested on suspicion of vandalism. Now Lucinda has her hands full, trying to prove Charley's innocence while also dealing with the repercussions of the reopened cases. "Multiple cases, interesting details of police work, and well-drawn characters, especially the complex, principled Lucinda, drive this fast-paced mystery that will appeal to readers who enjoy strong women protagonists." — Booklist This is the sixth book in the critically acclaimed Lucinda Pierce Mysteries by Edgar Award–winning true-crime writer Diane Fanning.